Time Expansion and Clear Speech to Improve Speechrecognition in Older Adults - . Supeno; Lusy Tunik Muharlisiani; Danny Yatika (International Conference on Education and Language (ICEL), 2014)
Speech understanding deficits are common in older adults. In addition to hearing sensitivity, changes in certain cognitive functions may affect speech recognition. One such change that may impact the ability to follow a rapidly changing speech signal is processing speed. When speakers slow the rate of their speech naturally in order to speak clearly, speech recognition is improved. The acoustic characteristics of naturally slowed speech are of interest in developing time-expansion algorithms to improve speech recognition for older listeners. In this study, we tested younger normally hearing, older normally hearing, and older hearing-impaired listeners on time-expanded speech using increased duration and increased intensity of unvoiced consonants. Although all groups performed best on unprocessed speech, performance with processed speech was better with the consonant gain feature without time expansion in the noise condition and better at the slowest time-expanded rate in the quiet condition. The effects of signal processing on speech recognition are discussed.